Termination of Employment Contract with Employees Carrying out Educational Functions - Karapetyan, Mane (Bulletin of Yerevan University C: Jurisprudence, 2023)
In the grounds for termination of the employment contract at the initiative of the employer, the legislator also included a ground for loss of confidence in the employee, the independent basis of which is the permission of an employee performing an educational function, an action incompatible with the continuation of work. Unlike a number of other grounds for termination of an employment contract, this basis is characterized by a lack of certainty and gives rise to heterogeneous interpretations. The problem is that the legislator clearly did not regulate, by what criteria should it be determined whether this or that act is compatible with the educational function or not? This article presents the institute of termination of an employment contract at the initiative of an employer with a person performing an educational function, existing scientific approaches to it, the experience of foreign countries and the judicial practice of the Republic of Armenia.